2004
DOI: 10.1194/jlr.m300425-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-l-carnitine supplementation restores decreased tissue carnitine levels and impaired lipid metabolism in aged rats

Abstract: The effects of long-term carnitine supplementation on age-related changes in tissue carnitine levels and in lipid metabolism were investigated. The total carnitine levels in heart, skeletal muscle, cerebral cortex, and hippocampus were ‫ف‬ 20% less in aged rats (22 months old) than in young rats (6 months old). On the contrary, plasma carnitine levels were not affected by aging. Supplementation of acetyl-l -carnitine (ALCAR; 100 mg/kg body weight/day for 3 months) significantly increased tissue carnitine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Panchamoorthy and Carani [39] reported that treated rats with L-carnitine caused a significant reduced in TG as compared to untreated rats. L-carnitine is known to promote the transport of cytosolic long-chain fatty acids into the mitochondrial matrix for -oxidation, thereby providing mitochondrial energy [40,41]. L-carnitine may lower plasma TG by increasing the utilization and/or oxidation of fatty acids for energy or possibly by altering very low-density lipoprotein synthesis [42].…”
Section: Resultsmentioning
confidence: 99%
“…Panchamoorthy and Carani [39] reported that treated rats with L-carnitine caused a significant reduced in TG as compared to untreated rats. L-carnitine is known to promote the transport of cytosolic long-chain fatty acids into the mitochondrial matrix for -oxidation, thereby providing mitochondrial energy [40,41]. L-carnitine may lower plasma TG by increasing the utilization and/or oxidation of fatty acids for energy or possibly by altering very low-density lipoprotein synthesis [42].…”
Section: Resultsmentioning
confidence: 99%
“…Panchamoorthy and Carani 22 reported that treated rats with L-carnitine caused a significant reduced in TG as compared to untreated rats. L-carnitine is known to promote the transport of cytosolic long-chain fatty acids into the mitochondrial matrix for β-oxidation, thereby providing mitochondrial energy 23,24 . L-carnitine may lower plasma TG by increasing the utilization and/or oxidation of fatty acids for energy or possibly by altering very low-density lipoprotein synthesis 25 .…”
Section: Alteration In Lipid Physiology and Biochemistry Of Mammalianmentioning
confidence: 99%
“…L-carnitine may lower plasma TG by increasing the utilization and/or oxidation of fatty acids for energy or possibly by altering very low-density lipoprotein synthesis 25 . The data gathered so far [22][23][24][25] reflect that the high density lipoprotein in rats was not affected (P > 0.05) as a consequence of the supplementation with 15% dried mushroom and 400 mg L-carnitine. However, rats supplemented with 450 mg mushroom extract and 800 mg L-carnitine had a higher (P ≤ 0.05) high density lipoprotein compared to those of the control sets.…”
Section: Alteration In Lipid Physiology and Biochemistry Of Mammalianmentioning
confidence: 99%
“…Rajasekar and Anuradha 35 reported that treated rats with L-carnitine caused a significant reduced in TG as compared to untreated rats. L-carnitine is known to promote the transport of cytosolic long-chain fatty acids into the mitochondrial matrix for $-oxidation, thereby providing mitochondrial energy 36,37 . L-carnitine may lower plasma TG by increasing the utilization and/or oxidation of fatty acids for energy or possibly by altering very low-density lipoprotein synthesis 38 .…”
Section: Alteration In Lipid Physiology and Biochemistry Of Mammalianmentioning
confidence: 99%